Protocatechuic Acid Alkyl Esters: Hydrophobicity As a Determinant Factor for Inhibition of NADPH Oxidase - de Faria, C. M. Q. G. [UNESP]; Nazare, A. C. [UNESP]; Petronio, M. S. [UNESP]; Paracatu, L. C. [UNESP]; Zeraik, M. L. [UNESP]; Regasini, L. O. [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; da Fonseca, L. M. [UNESP]; Ximenes, V. F. [UNESP] (Bentham Science Publ Ltd, 2012)
This study presents the increased efficiency of NADPH oxidase inhibition produced by esterification of protocatechuic acid (P0). Alkyl esters bearing chain lengths of 4 (P4), 7 (P7) and 10 (P10) carbons were synthesized and their oxidation potential, hydrophobicity, antiradical activity, inhibition of superoxide anion (O-2(center dot-)), and the abilities to affect hypochlorous acid (HOCl) production by leukocytes and inhibit myeloperoxidase (MPO) chlorinating activity were studied. The increased hydrophobicity (logP, 0.81-4.82) of the esters was not correlated with a significant alteration in their oxidation potential (0.222-0.298 V). However, except for P10, the esters were similar to 2-fold more effective than the acid precursor for the scavenging of DPPH and peroxyl radicals. The esters were strong inhibitors of O2 released by activated neutrophils (PMNs) and peripheral blood mononuclear cells (PBMCs). A correlation was found between the carbon chain length and the relative inhibitory potency. P7, the most active ester, was similar to 10-fold more efficient as NADPH oxidase inhibitor than apocynin. The esters strongly inhibited the release of HOCl by PMNs, which was a consequence of the inhibition of NADPH oxidase activity in these cells. In conclusion, as effective inhibitors of NADPH oxidase, the esters of protocatechuic acid are promising drugs for treatment of chronic inflammatory diseases. Moreover, this is the first demonstration that, besides the redox active moiety, the hydrophobicity can also be a determinant factor for the design of NADPH oxidase inhibitors.